An insight into entrepreneurship education practices in Technical and Vocational Education and Training institutions - Abede Jawara Mack; Daniel White; Osiris Senghor (Journal of Global Entrepreneurship Research, 2019)
Technical and Vocational Education and Training (TVET) and entrepreneurship education have always been used as a vehicle towards economic and social transformation within many nations. With this in mind, the research investigates the entrepreneurship education practices in TVET institutions in Trinidad and Tobago. A quantitative study utilising a face-to-face survey was conducted with 446 TVET students from four TVET institutions from all geographical locations in Trinidad and Tobago. Correlation analysis and logistic regression were performed to assess the views and significant relationships involving students' interest and entrepreneurship education practices. The results of this study have important implications for TVET institutions. Students' interest in pursuing entrepreneurship was very high, and it tells a very good narrative that persons want to be an entrepreneur. Survey data revealed that 98% of respondents were interested in pursuing entrepreneurship as a career path. However, with the absence of an adequate platform or systems at the TVET institutions, students are not engaged in entrepreneurial paths in any significant way.
Keywords: 650; Entrepreneur; Entrepreneurship; Entrepreneurship education; Skills training; TVET; TVET institution; Trinidad and Tobago